2013
DOI: 10.1037/a0029562
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors in college students' attitudes toward seeking professional psychological help: A meta-analysis.

Abstract: This study examines the relationships between attitudes toward seeking professional psychological help, which was determined with the Attitude Toward Seeking Professional Psychological Help Scale, and relevant psychological variables. For this study, the authors narrowed the study field to 19, which included a total of 7,397 participants, and used the MIX (Meta-analysis with Interactive eXplanations) program. The following 9 variables were chosen for the study: anticipated benefit, anticipated risks, depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
120
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 54 publications
20
120
1
5
Order By: Relevance
“…For example, Heffner and Eisenberg's (2009) survey of college students revealed that students reporting low-quality peer support were six times more likely to experience depressive symptoms than students with high-quality support. Meta-analysis results (e.g., Nam et al, 2013) have also found peer support to be positively associated with greater help-seeking behavior by college students. Despite the success associated with support, organizations offering peer support for depressed people are often unavailable due to scarcity (Davidson, Potter, Ross, & Public, 1999), highlighting the need for effective ways to elicit social support for depressed persons.…”
Section: Figures Released By the World Health Organizationmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, Heffner and Eisenberg's (2009) survey of college students revealed that students reporting low-quality peer support were six times more likely to experience depressive symptoms than students with high-quality support. Meta-analysis results (e.g., Nam et al, 2013) have also found peer support to be positively associated with greater help-seeking behavior by college students. Despite the success associated with support, organizations offering peer support for depressed people are often unavailable due to scarcity (Davidson, Potter, Ross, & Public, 1999), highlighting the need for effective ways to elicit social support for depressed persons.…”
Section: Figures Released By the World Health Organizationmentioning
confidence: 90%
“…Social support is often a target goal in mental health advocacy, particularly for university students, as it can be effective method for reducing depression (Heffner & Eisenberg, 2009;Nam et al, 2013;Kendler, Myers, & Prescott, 2005), it leads to decreased suicide attempts (Compton, Thompson, & Kaslow, 2005), and support can come from people without formal medical training, such as other students (Kendler, Myers, & Prescott, 2005). For example, Heffner and Eisenberg's (2009) survey of college students revealed that students reporting low-quality peer support were six times more likely to experience depressive symptoms than students with high-quality support.…”
Section: Figures Released By the World Health Organizationmentioning
confidence: 99%
“…Similarly, suicidal ideation appears to be negatively related to adolescents' help‐seeking intentions from family and friends (Deane, Wilson, & Ciarrochi, ; Wilson, Deane, & Ciarrochi, ). Moreover, several studies have found negative relationships between depressive symptoms and attitudes toward seeking professional psychological help (Calhoun & Selby, ; Garland & Zigler, ; Nam et al., ).…”
Section: Predictors Of Help‐seekingmentioning
confidence: 99%
“…The initial database search was deliberately kept broad to maximize identification of studies (31). Reference lists of all eligible articles, relevant meta-analyses, and reviews (5,9,16,24,(32)(33)(34)(35) were manually searched for additional eligible studies.…”
Section: Literature Searchmentioning
confidence: 99%